The complete mitochondrial genome sequence of the edible mushroom Stropharia rugosoannulata (Strophariaceae, Basidiomycota). Issue 1 (2nd January 2019) - Suzuki, Tomohiro; Ono, Akiko; Choi, Jae-Hoon; Wu, Jing; Kawagishi, Hirokazu; Dohra, Hideo
Abstract: Stropharia rugosoannulata (Strophariaceae, Basidiomycota) is an edible mushroom distributed in northern temperate zones throughout the world. In this study, the complete mitochondrial genome sequence of S. rugosoannulata was determined. This mitochondrial genome is 60, 551 bp in length with a GC content of 31.0% and encodes 14 conserved proteins, 2 ribosomal RNAs, 29 transfer RNAs, and 12 further ORFs. Phylogenetic relationships based on the mitochondrial genome between S. rugosoannulata and other basidiomycetes are inconsistent with those based on nuclear genes. This is the first report of the mitochondrial genome of mushrooms belonging to the family Strophariaceae.